2021
DOI: 10.1155/2021/9921897
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Attenuates LPS-Induced Macrophage Inflammation In Vitro and Sepsis-Induced Vascular Inflammation In Vivo by Upregulating miR-29a-5p Expression

Abstract: Excessive release of cytokines such as IL-1β and other inflammatory mediators synthesized and secreted by macrophages is the fundamental link of uncontrolled inflammatory response in sepsis. 17β-Estradiol (E2) plays anti-inflammatory and vascular protective effects by regulating leukocyte infiltration and the expression of chemokines or cytokines induced by injury. However, the role of E2 in the inflammatory response of macrophages in sepsis and its mechanism are still not fully understood. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…As shown in Table 1, miR-29a-5p and sclerostin showed higher expression, but the fetuin-A expression was lower in the study group than in the control group, indicating seases, as reported in several studies (11). In this study, miR-29a-5p was further found to be highly expressed in CKD patients and positively correlated with vascular calcification (r=0.695, p=0.001) as its expression increased when patients developed vascular calcification.…”
Section: Expression Of Mir-29a-5p Sclerostin and Fetuin-a In Both Groupssupporting
confidence: 78%
“…As shown in Table 1, miR-29a-5p and sclerostin showed higher expression, but the fetuin-A expression was lower in the study group than in the control group, indicating seases, as reported in several studies (11). In this study, miR-29a-5p was further found to be highly expressed in CKD patients and positively correlated with vascular calcification (r=0.695, p=0.001) as its expression increased when patients developed vascular calcification.…”
Section: Expression Of Mir-29a-5p Sclerostin and Fetuin-a In Both Groupssupporting
confidence: 78%
“…It was found that E 2 can modulate the expression of the inflammatory factors in immune cells to exert beneficial effects. ( 9 , 15 ) Although inflammatory factors can impair vascular functions to prompt the development of pathophysiological progression,( 16 ) it remains a mystery for E 2 to modulate inflammatory factors in vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in studies on the critical roles of trophoblasts in the pathogenesis of RPL, LPS-induced M1 macrophage polarization suppressed trophoblast migration and invasion [ 13 , 22 ]. Interestingly, 17ß-estradiol (E 2 ) has been reported to attenuate LPS-induced elevation of TLR4 and macrophage inflammation [ 23 , 24 ]. Recently, E 2 was demonstrated to facilitate the resolution of pro-inflammation conditions by enhancing the polarization of M1 to M2 macrophages, thereby conferring cardioprotection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%